Pancasila: The Foundation for Developing Science and Technology in Indonesia - Nabila, Liliana; Mardatillah, Dwi; Marjani, Halwa; Quratu Aini, Asyifa; Rahmad Fauzan, Daffa; Br Sembiring, Aprilia (Borneo Novelty Publishing, 2024)
Pancasila, as the foundation of the Indonesian state, has an important role in the development of science and technology. Pancasila reflects the noble values ​​that serve as the ideological foundation and ethical and moral guidelines in the development of sustainable and equitable science and technology. This study employs a qualitative approach, utilising books, journals, and relevant articles. This study aims to explain the importance of the role of Pancasila in the advancement of science and technology by applying the values ​​of Pancasila as the basis for the development of science and technology. The results of this study indicate that Pancasila is not only the foundation of the state but also a strong ideological foundation for the development of sustainable and equitable science and technology by applying the values ​​of Pancasila.